SISTEM INFORMASI OPERASIONAL UMKM BERBASIS PROGRESSIVE WEB APP (PWA) UNTUK PENGELOLAAN ABSENSI KARYAWAN BERBASIS GEOLOCATION DAN LAPORAN KEUANGAN PADA UMKM SEMPOL AYAM RATIH TEGAL - Sofiullah Abi Sadzili; Slamet Wiyono; Syefudin Syefudin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Ratih Chicken Sempol MSME in Tegal continues to face challenges in managing its operational data, particularly in employee attendance and financial reporting, which are still handled manually and are not yet integrated. Employee attendance is recorded through a WhatsApp group by submitting photos as proof of attendance, while financial records are maintained separately using handwritten notebooks and Microsoft Excel. As a result, the data are not stored in a centralized system, making data management, retrieval, and recapitulation less efficient and more prone to recording errors. This study aims to design and develop a geolocation-based employee attendance system and a financial reporting system based on a Progressive Web App (PWA), integrated into a single platform to support the operational data management of Ratih Chicken Sempol MSME in Tegal. The system was developed using the Waterfall methodology, with PHP as the programming language, the Laravel framework, and MySQL as the database management system. System testing was conducted using the Black Box Testing method. The system utilizes geolocation technology to validate employee attendance locations and provides a financial reporting module in the form of a General Cash Book (GCB) to centrally manage financial transactions. Based on the testing results, all system functionalities operated according to the specified requirements. The developed system successfully supports location-validated employee attendance and integrated financial reporting, thereby improving the effectiveness and efficiency of operational data management.